Evaluation of a school-based peer leader bicycle helmet intervention - Hall, M.; Cross, D.; Howat, Peter; Stevenson, M.; Shaw, Therese (Taylor and Francis, 2004)
Objectives. Bicycle-related injury remains a major cause of death and injury hospitalization among Australian children. The study aimed to assess the effectiveness of a whole-school intervention to increase the correct wearing of bicycle helmets by primary school children. Methods. A randomized intervention trial was conducted in 27 Western Australian primary schools. A major component of the intervention was a peer-led classroom curriculum for 10?12 year old children. Helmet use by cyclists was observed as children were leaving school at baseline (May 2000) and after the first year and second year of the intervention. A cohort of 10?11 year old children in study schools completed a self-administered questionnaire at the same three data collection points.Results. Over the 2 years of the study, observed helmet wearing rates declined by 13% in the control group (from 93% at baseline to 80% at post-test 2) and by 5% in the intervention group (from 89% to 84%) (F = 1.745, p = 0.185). Among the Grade 5/6 cohort students who were regular riders, the likelihood of reporting always wearing a helmet was 1.9 times higher at post-test 1 (z = 2.51, p = 0.012) and 1.7 times higher at post-test 2 (z = 2.13, p = 0.033) for the intervention group than the control group students who did not always wear a helmet at baseline. Conclusions. The data suggest that school-based activities can arrest the rate of decline in helmet use by children. Using peer teachers is a useful strategy to engage students in normative-based protective behaviours. The logistical challenges this strategy presents appear to be worth the outcomes.